2023
DOI: 10.1038/s41392-023-01556-8
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike protein receptor-binding domain perturbates intracellular calcium homeostasis and impairs pulmonary vascular endothelial cells

Abstract: Exposure to the spike protein or receptor-binding domain (S-RBD) of SARS-CoV-2 significantly influences endothelial cells and induces pulmonary vascular endotheliopathy. In this study, angiotensin-converting enzyme 2 humanized inbred (hACE2 Tg) mice and cultured pulmonary vascular endothelial cells were used to investigate how spike protein/S-RBD impacts pulmonary vascular endothelium. Results show that S-RBD leads to acute-to-prolonged induction of the intracellular free calcium concentration ([Ca2+]i) via ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Supporting this suggestion of a direct effect on the endothelium are the results of a recently published study in in-vivo ACE2 humanized inbred mice and in-vitro cultured human and mice pulmonary vascular endothelial cells that demonstrated that the receptor binding domain of the SARS-CoV-2 virus caused pulmonary vascular endothelial damage in part by upregulating Orai1 and triggering calcium in ux. 27 Treatment with Auxora would block this calcium in ux and consequently prevent endothelial damage independently of a decrease in systemic in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this suggestion of a direct effect on the endothelium are the results of a recently published study in in-vivo ACE2 humanized inbred mice and in-vitro cultured human and mice pulmonary vascular endothelial cells that demonstrated that the receptor binding domain of the SARS-CoV-2 virus caused pulmonary vascular endothelial damage in part by upregulating Orai1 and triggering calcium in ux. 27 Treatment with Auxora would block this calcium in ux and consequently prevent endothelial damage independently of a decrease in systemic in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of Piezo1 using GsMTx4 effectively prevents disruption of intracellular calcium homeostasis in endothelial cells. These findings strongly suggest that targeting Piezo1 could be a potential therapeutic strategy for mitigating S-RBD-induced pulmonary vascular damage, offering novel insights into the management of COVID-associated pulmonary vascular diseases and long-term complications in individuals with long COVID ( 96 ). It has been also reported to enhance lung endothelial barrier function and mitigate ventilator-induced lung injury by suppressing Src-induced VE-cadherin phosphorylation ( 7 ).…”
Section: Potential Roles Of Endothelial Piezo1 In Covid-19mentioning
confidence: 94%
“…The spike protein of SARS-CoV-2 features a critical region known as the spike protein receptor-binding domain (S-RBD), which exhibits a high affinity for human ACE-2 receptors and is crucial for viral entry ( 94 , 95 ). S-RBD has been implicated in inducing an acute to prolonged increase in intracellular calcium concentration in human pulmonary arterial endothelial cells, which is associated with the activation and expression of Piezo1 and store-operated calcium channels (SOCC) ( 96 ). The SARS-CoV-2 induced persistent perturbation of intracellular calcium homeostasis, driven by the upregulation of Piezo1 and other calcium channels, may lead to elevated apoptosis and impairment of pulmonary vascular endothelial cells, contributing to the vascular complications observed in severe COVID-19 cases.…”
Section: Potential Roles Of Endothelial Piezo1 In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations